Polarizing plate and image display device
The polarizing plate with a urea-based adhesive and cyclodextrins maintains transmittance and polarization by suppressing polyenization, addressing the issue of decreased performance in high-temperature environments.
Patent Information
- Application Number
- JP2021034950
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-05
- Publication Date
- 2024-12-23
- Estimated Expiration
- 2041-03-05
AI Technical Summary
Polarizing plates used in image display devices experience significant decreases in transmittance and degree of polarization in high-temperature environments, particularly when employed in interlayer filling configurations.
A polarizing plate comprising a polarizing element with a dichroic dye adsorbed on a polyvinyl alcohol resin layer, bonded to a transparent protective film via an adhesive containing a urea-based compound and cyclodextrins, with specific content ratios and water content control to suppress polyenization.
The solution effectively maintains transmittance and polarization in high-temperature environments, preventing significant decreases even after exposure to 105°C for extended periods.
Smart Images

Figure 0007604271000001 
Figure 0007604271000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a polarizing plate and an image display device. [Background technology]
[0002] Liquid crystal display devices (LCDs) are widely used not only in liquid crystal televisions, but also in personal computers, mobile devices such as mobile phones, and in-vehicle applications such as car navigation systems. Typically, liquid crystal display devices have a liquid crystal panel with polarizing plates attached to both sides of a liquid crystal cell with an adhesive, and display is performed by controlling light from a backlight with the liquid crystal panel. In recent years, organic electroluminescence (EL) display devices have also been widely used in televisions, mobile devices such as mobile phones, and in-vehicle applications such as car navigation systems, similar to liquid crystal display devices. In organic EL display devices, a circular polarizing plate (a laminate including a polarizing element and a λ / 4 plate) may be placed on the viewing side surface of the image display panel to prevent external light from being reflected by a metal electrode (cathode) and being viewed as a mirror surface.
[0003] As mentioned above, polarizing plates are increasingly being installed in vehicles as components of image display devices such as liquid crystal display devices, organic electroluminescence display devices, etc. Polarizing plates used in in-vehicle image display devices are more often exposed to high-temperature environments than those used in mobile applications such as televisions and mobile phones, and are therefore required to have small changes in properties at high temperatures (high-temperature durability).
[0004] On the other hand, for the purpose of preventing damage to the image display panel due to impact from the outer surface, a configuration in which a front panel such as a transparent resin plate or a glass plate (also called a "window layer") is provided on the viewing side of the image display panel is increasingly being adopted. In image display devices equipped with a touch panel, a configuration in which the touch panel is provided on the viewing side of the image display panel and a front panel is provided on the further viewing side of the touch panel is widely adopted.
[0005] In such a configuration, if there is an air layer between the image display panel and a transparent member such as a front plate or a touch panel, the external light is reflected at the interface of the air layer, and the visibility of the screen tends to decrease. Therefore, there is a growing trend to adopt a configuration (hereinafter, sometimes referred to as an "interlayer filling configuration") in which the space between the polarizing plate and the transparent member arranged on the viewing side surface of the image display panel is filled with a layer other than the air layer, which is usually a solid layer (hereinafter, sometimes referred to as an "interlayer filling agent"). The interlayer filling agent is preferably a material whose refractive index is close to that of the polarizing plate or the transparent member. As the interlayer filling agent, a pressure sensitive adhesive or a UV curable adhesive is used for the purpose of suppressing the decrease in visibility due to the reflection at the interface and bonding and fixing each member (see, for example, Patent Document 1).
[0006] The interlayer filling structure is being widely adopted for mobile applications such as mobile phones that are often used outdoors. In addition, due to the increasing demand for visibility in recent years, the adoption of an interlayer filling structure in which a front transparent plate is placed on the surface of an image display panel and an adhesive layer or the like is filled between the panel and the front transparent plate is being considered for in-vehicle applications such as car navigation devices.
[0007] However, it has been reported that when such a configuration is adopted, the transmittance of the polarizing plate significantly decreases in a high-temperature environment. As a solution to this problem, Patent Document 2 proposes a method of suppressing the decrease in transmittance by setting the moisture content per unit area of the polarizing plate to a specified amount or less and setting the saturated water absorption amount of the transparent protective film adjacent to the polarizing element to a specified amount or less. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] Japanese Patent Application Publication No. 11-174417 [Patent Document 2] JP 2014-102353 A Summary of the Invention [Problem to be solved by the invention]
[0009] However, even such a polarizing plate does not have a sufficient effect of suppressing a decrease in transmittance in a high-temperature environment. An object of the present invention is to provide a novel polarizing plate capable of suppressing a decrease in transmittance in a high-temperature environment, and an image display device using the polarizing plate. [Means for solving the problem]
[0010] The present invention provides a polarizing plate and an image display device as exemplified below. [1] A polarizing plate comprising a polarizing element having a polyvinyl alcohol-based resin layer on which a dichroic dye is adsorbed and oriented, and a transparent protective film laminated on at least one surface of the polarizing element, the polarizing element and the transparent protective film are attached to each other by an adhesive layer formed from an adhesive containing a urea compound and a cyclodextrin; The urea compound is at least one selected from the group consisting of urea, urea derivatives, thiourea, and thiourea derivatives. [2] The polarizing plate according to [1], wherein the adhesive contains at least one urea compound selected from the group consisting of urea derivatives and thiourea derivatives. [3] The polarizing plate according to [1] or [2], wherein the adhesive contains a polyvinyl alcohol-based resin. [4] The polarizing plate according to [3], wherein the content of the urea compound in the adhesive is 0.1 parts by mass or more and 400 parts by mass or less per 100 parts by mass of the polyvinyl alcohol-based resin. [5] The polarizing plate according to [3] or [4], wherein the adhesive contains cyclodextrins in an amount of 1 part by mass or more and 50 parts by mass or less per 100 parts by mass of the polyvinyl alcohol-based resin. [6] The polarizing plate according to any one of [1] to [5], wherein the adhesive layer has a thickness of 0.01 μm or more and 7 μm or less. [7] The polarizing plate according to any one of [1] to [6], wherein the cyclodextrin is at least one selected from the group consisting of α-cyclodextrin, β-cyclodextrin, and γ-cyclodextrin. [8] The polarizing plate according to any one of [1] to [7], wherein the moisture content of the polarizing element is equal to or higher than the equilibrium moisture content at a temperature of 20° C. and a relative humidity of 30% and equal to or lower than the equilibrium moisture content at a temperature of 20° C. and a relative humidity of 50%. [9] The polarizing plate according to any one of [1] to [7], wherein the moisture content of the polarizing plate is equal to or higher than the equilibrium moisture content at a temperature of 20° C. and a relative humidity of 30% and equal to or lower than the equilibrium moisture content at a temperature of 20° C. and a relative humidity of 50%.
[10] The polarizing plate is used in an image display device, The polarizing plate according to any one of [1] to [9], wherein in the image display device, solid layers are provided on both sides of the polarizing plate in contact with each other.
[11] An image display device comprising: an image display cell; a first pressure-sensitive adhesive layer laminated on a viewing-side surface of the image display cell; and a polarizing plate according to any one of [1] to
[10] laminated on the viewing-side surface of the first pressure-sensitive adhesive layer.
[12] The image display device described in
[11] , further comprising a second adhesive layer laminated on the viewing side surface of the polarizing plate, and a transparent member laminated on the viewing side surface of the second adhesive layer.
[13] The image display device according to
[12] , wherein the transparent member is a glass plate or a transparent resin plate.
[14] The image display device according to
[12] , wherein the transparent member is a touch panel. Effect of the Invention
[0011] According to the present invention, it is possible to provide a polarizing plate having improved high-temperature durability. According to the present invention, it is possible to provide a polarizing plate in which the decrease in transmittance due to high temperatures is suppressed even when used in an image display device having an interlayer filling configuration. Furthermore, by using the polarizing plate according to the present invention, it is possible to provide an image display device in which the decrease in transmittance in a high-temperature environment is suppressed. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] Hereinafter, an embodiment of the present invention will be described, however, the present invention is not limited to the following embodiment.
[0013] [Polarizing plate] A polarizing plate according to an embodiment of the present invention includes a polarizing element having a dichroic dye adsorbed and aligned in a layer containing a polyvinyl alcohol resin, and a transparent protective film. The polarizing element and the transparent protective film are bonded together with an adhesive layer formed from an adhesive containing a urea compound and cyclodextrins. The polarizing plate according to this embodiment preferably has at least one of the following characteristics (a) and (b). (a) The moisture content of the polarizing element is equal to or greater than the equilibrium moisture content at a temperature of 20° C. and a relative humidity of 30% and equal to or less than the equilibrium moisture content at a temperature of 20° C. and a relative humidity of 50%. (b) The moisture content of the polarizing plate is equal to or greater than the equilibrium moisture content at a temperature of 20° C. and a relative humidity of 30% and equal to or less than the equilibrium moisture content at a temperature of 20° C. and a relative humidity of 50%.
[0014] As a conventional polarizing plate having excellent high-temperature durability, for example, a polarizing plate in which the decrease in transmittance is suppressed even when the polarizing plate is left alone in an environment at a temperature of 95° C. for 1000 hours is known. However, even such a polarizing plate, when used in an interlayer filling configuration, may show a significant decrease in transmittance and polarization degree in the center of the polarizing plate plane when left in an environment at a temperature of 105° C. for 240 hours. The significant decrease in transmittance and polarization degree of a polarizing plate in a high-temperature environment is considered to be a problem that is particularly likely to occur when an image display device employing an interlayer filling configuration in which one surface of a polarizing plate is bonded to an image display cell and the other surface is bonded to a transparent member such as a touch panel or a front panel is exposed to a high-temperature environment.
[0015] The polarizing plate with a significantly reduced transmittance due to the interlayer filling structure was measured by Raman spectroscopy at 1100 cm -1 near (derived from the C-C bond) and 1500 cm -1 Since there is a peak near the -C=C bond, it is considered to be a polyene structure (-C=C). nThe polyene structure is presumably formed when the polyvinyl alcohol constituting the polarizing element is dehydrated to form a polyene structure (Patent Document 2, paragraph
[0012] ).
[0016] The polarizing plate according to the present invention can further improve high-temperature durability. When incorporated in an image display device having an interlayer filling structure, the polarizing plate according to the present invention can suppress a decrease in transmittance and polarization degree even when exposed to a high-temperature environment of, for example, a temperature of 105° C.
[0017] <Polarizing element> A well-known polarizing element can be used as the polarizing element in which a dichroic dye is adsorbed and aligned in a layer containing a polyvinyl alcohol (hereinafter also referred to as "PVA")-based resin (hereinafter also referred to as a "PVA-based resin layer"). Examples of the polarizing element include a stretched film obtained by dyeing a PVA-based resin film with a dichroic dye and uniaxially stretching it, and a stretched layer obtained by using a laminated film having a coating layer formed by applying a coating liquid containing a PVA-based resin onto a base film, dyeing the coating layer with a dichroic dye, and uniaxially stretching the laminated film. The stretching may be performed after dyeing with the dichroic dye, may be performed while dyeing, or may be performed after stretching and dyeing.
[0018] PVA resins are obtained by saponifying polyvinyl acetate resins. Examples of polyvinyl acetate resins include polyvinyl acetate, which is a homopolymer of vinyl acetate, and copolymers of vinyl acetate with other monomers that can be copolymerized with it. Examples of other copolymerizable monomers include unsaturated carboxylic acids, olefins such as ethylene, vinyl ethers, and unsaturated sulfonic acids.
[0019] The saponification degree of the PVA resin is preferably about 85 mol% or more, more preferably about 90 mol% or more, and even more preferably about 99 mol% or more and 100 mol% or less. The polymerization degree of the PVA resin is, for example, 1000 to 10000, preferably 1500 to 5000. The PVA resin may be modified, and may be, for example, polyvinyl formal, polyvinyl acetal, polyvinyl butyral, etc., modified with aldehydes.
[0020] The thickness of the polarizing element is preferably 3 μm or more and 35 μm or less, more preferably 4 μm or more and 30 μm or less, and even more preferably 5 μm or more and 25 μm or less. By making the thickness of the polarizing element 35 μm or less, the influence of the polyenation of the PVA resin on the deterioration of optical properties in a high temperature environment can be suppressed. By making the thickness of the polarizing element 3 μm or more, it becomes easy to make a configuration that achieves the desired optical properties.
[0021] The polarizing element preferably contains a urea-based compound and cyclodextrins. In this embodiment, the polarizing element and the transparent protective film are bonded together by an adhesive layer formed from an adhesive containing a urea-based compound and cyclodextrins, and therefore it is presumed that a part of the urea-based compound and a part of the cyclodextrins are transferred from the adhesive layer and are contained in the polarizing element. The urea-based compound and cyclodextrins in the polarizing element may contain those added during the manufacturing process of the polarizing element. By providing a polarizing element containing a urea-based compound and cyclodextrins, the transmittance is unlikely to decrease even when the polarizing plate is exposed to a high-temperature environment. In addition, by providing an adhesive layer containing a urea-based compound and cyclodextrins, the decrease in the polarization degree can be suppressed even when the polarizing plate is exposed to a high-temperature environment. When two polarizing plates are used in a cross-Nicol relationship, if the polarization degree of the polarizing plate decreases, light leakage (hereinafter also referred to as "cross leakage") is likely to occur. However, according to the present invention, the polarization degree is unlikely to decrease even when exposed to a high-temperature environment, and therefore cross leakage is also easily suppressed. This is presumably because the urea compounds and cyclodextrins contained in the polarizing element suppress the polyenization of the PVA resin.
[0022] The method of incorporating a urea compound and a cyclodextrin in a polarizing element includes a method of immersing a PVA resin layer in a treatment solvent containing a urea compound and / or a cyclodextrin, or a method of spraying, flowing or dropping the treatment solvent onto a PVA resin layer. Among these, the method of immersing a PVA resin layer in a treatment solvent containing both a urea compound and a cyclodextrin is preferably used.
[0023] The process of immersing the PVA-based resin layer in a treatment solvent containing a urea-based compound and cyclodextrins may be carried out simultaneously with the processes of swelling, stretching, dyeing, crosslinking, washing, etc. in the manufacturing method of a polarizing element described later, or may be provided separately from these processes. The process of making the PVA-based resin layer contain a urea-based compound and cyclodextrins is preferably carried out after dyeing the PVA-based resin layer with iodine, and more preferably carried out simultaneously with the crosslinking process after dyeing. According to such a method, the hue change is small, and the influence on the optical properties of the polarizing element can be reduced.
[0024] In order to incorporate the urea compound and the cyclodextrins in the polarizing element, they may be added both during the manufacture of the polarizing element and to the adhesive. Alternatively, one of the urea compound and the cyclodextrins may be incorporated during the manufacture of the polarizing element and the other or both may be incorporated in the adhesive, or both may be incorporated during the manufacture of the polarizing element and one may be incorporated in the adhesive.
[0025] (Urea-based compounds) The urea-based compound is at least one selected from the group consisting of urea, urea derivatives, thiourea, and thiourea derivatives. The urea-based compounds can be used alone or in combination of two or more. Urea-based compounds include water-soluble and poorly water-soluble urea-based compounds, and either type of urea-based compound can be used. When a poorly water-soluble urea-based compound is used in a water-soluble adhesive, it is preferable to devise a dispersion method so that an increase in haze does not occur after the adhesive layer is formed.
[0026] (urea derivative) A urea derivative is a compound in which at least one of the four hydrogen atoms of a urea molecule is substituted with a substituent. In this case, the substituent is not particularly limited, but is preferably a substituent consisting of a carbon atom, a hydrogen atom, and an oxygen atom.
[0027] Specific examples of urea derivatives include mono-substituted ureas such as methylurea, ethylurea, propylurea, butylurea, isobutylurea, N-octadecylurea, 2-hydroxyethylurea, hydroxyurea, acetylurea, allylurea, 2-propynylurea, cyclohexylurea, phenylurea, 3-hydroxyphenylurea, (4-methoxyphenyl)urea, benzylurea, benzoylurea, o-tolylurea, and p-tolylurea.
[0028] Disubstituted ureas include 1,1-dimethylurea, 1,3-dimethylurea, 1,1-diethylurea, 1,3-diethylurea, 1,3-bis(hydroxymethyl)urea, 1,3-tert-butylurea, 1,3-dicyclohexylurea, 1,3-diphenylurea, 1,3-bis(4-methoxyphenyl)urea, 1-acetyl-3-methylurea, 2-imidazolidinone (ethylene urea), and tetrahydro-2-pyrimidinone (propylene urea).
[0029] Examples of 4-substituted ureas include tetramethylurea, 1,1,3,3-tetraethylurea, 1,1,3,3-tetrabutylurea, 1,3-dimethoxy-1,3-dimethylurea, 1,3-dimethyl-2-imidazolidinone, and 1,3-dimethyl-3,4,5,6-tetrahydro-2(1H)-pyrimidinone.
[0030] (Thiourea derivatives) A thiourea derivative is a compound in which at least one of the four hydrogen atoms of a thiourea molecule is substituted with a substituent. In this case, the substituent is not particularly limited, but is preferably a substituent consisting of a carbon atom, a hydrogen atom, and an oxygen atom.
[0031] Specific examples of thiourea derivatives include mono-substituted thioureas such as N-methylthiourea, ethylthiourea, propylthiourea, isopropylthiourea, 1-butylthiourea, cyclohexylthiourea, N-acetylthiourea, N-allylthiourea, (2-methoxyethyl)thiourea, N-phenylthiourea, (4-methoxyphenyl)thiourea, N-(2-methoxyphenyl)thiourea, N-(1-naphthyl)thiourea, (2-pyridyl)thiourea, o-tolylthiourea, and p-tolylthiourea.
[0032] Examples of the disubstituted thiourea include 1,1-dimethylthiourea, 1,3-dimethylthiourea, 1,1-diethylthiourea, 1,3-diethylthiourea, 1,3-dibutylthiourea, 1,3-diisopropylthiourea, 1,3-dicyclohexylthiourea, N,N-diphenylthiourea, N,N'-diphenylthiourea, 1,3-di(o-tolyl)thiourea, 1,3-di(p-tolyl)thiourea, 1-benzyl-3-phenylthiourea, 1-methyl-3-phenylthiourea, N-allyl-N'-(2-hydroxyethyl)thiourea, and ethylenethiourea.
[0033] An example of the 3-substituted thiourea is trimethylthiourea, and an example of the 4-substituted thiourea is tetramethylthiourea or 1,1,3,3-tetraethylthiourea.
[0034] Among the urea-based compounds, urea derivatives or thiourea derivatives are preferred, and urea derivatives are more preferred, in that when used in an image display device with an interlayer filling structure, the decrease in transmittance in a high-temperature environment is suppressed and the decrease in polarization degree is small (the cross-drop is suppressed). Among the urea derivatives, mono- or di-substituted ureas are preferred, and mono-substituted ureas are more preferred. Di-substituted ureas include 1,1-substituted ureas and 1,3-substituted ureas, and 1,3-substituted ureas are more preferred.
[0035] (Cyclodextrins) Cyclodextrin is a non-reducing cyclic oligosaccharide in which glucose is bonded in a ring shape by α-1,4 bond. The more glucose units that constitute cyclodextrins, the larger the inner diameter of the cavity in the molecule. The cyclodextrins used in the present invention preferably contain 6 or more glucose units, and examples of such cyclodextrins include α-, β-, γ-, and δ-cyclodextrins that contain 6, 7, 8, and 9 glucose units, respectively. Cyclodextrins include α-, β-, γ-, and δ-cyclodextrins, as well as branched cyclodextrins having oligosaccharides such as glucose and maltose on the branched sugar chain. Cyclodextrins include cyclodextrin derivatives in which alkyl groups such as methyl groups; hydroxyalkyl groups such as 2-hydroxyethyl groups, 2-hydroxypropyl groups, 2,3-dihydroxypropyl groups, and 2-hydroxybutyl groups are bonded to the above cyclodextrins or branched cyclodextrins. The cyclodextrins can be used alone or in combination of two or more.
[0036] (Feature (a)) In the case of the characteristic (a), the moisture content of the polarizing element is equal to or higher than the equilibrium moisture content at a temperature of 20° C. and a relative humidity of 30%, and equal to or lower than the equilibrium moisture content at a temperature of 20° C. and a relative humidity of 50%. The moisture content of the polarizing element is preferably equal to or lower than the equilibrium moisture content at a temperature of 20° C. and a relative humidity of 45%, more preferably equal to or lower than the equilibrium moisture content at a temperature of 20° C. and a relative humidity of 42%, and even more preferably equal to or lower than the equilibrium moisture content at a temperature of 20° C. and a relative humidity of 38%. If the moisture content of the polarizing element is lower than the equilibrium moisture content at a temperature of 20° C. and a relative humidity of 30%, the polarizing element becomes less easy to handle and more likely to break. If the moisture content of the polarizing element is higher than the equilibrium moisture content at a temperature of 20° C. and a relative humidity of 50%, the transmittance of the polarizing element is more likely to decrease. It is presumed that if the moisture content of the polarizing element is high, the PVA resin is more likely to be polyenized. The moisture content of the polarizing element is the moisture content of the polarizing element in the polarizing plate.
[0037] A method for checking whether the moisture content of a polarizing element is within the range of equal to or greater than the equilibrium moisture content at a temperature of 20°C and a relative humidity of 30% and equal to or less than the equilibrium moisture content at a temperature of 20°C and a relative humidity of 50% can be to store the polarizing element in an environment adjusted to the above temperature and relative humidity ranges, and if there is no change in mass for a certain period of time, it can be deemed to have reached equilibrium with the environment. Alternatively, the equilibrium moisture content of the polarizing element in an environment adjusted to the above temperature and relative humidity ranges can be calculated in advance, and the moisture content of the polarizing element can be compared with the previously calculated equilibrium moisture content.
[0038] Methods for producing a polarizing element having a moisture content equal to or greater than the equilibrium moisture content at a temperature of 20°C and a relative humidity of 30% and equal to or less than the equilibrium moisture content at a temperature of 20°C and a relative humidity of 50% include, but are not limited to, a method in which the polarizing element is stored in an environment adjusted to the above-mentioned temperature and relative humidity range for 10 minutes to 3 hours, or a method in which the polarizing element is heated at 30°C to 90°C.
[0039] Another preferred method for producing a polarizing element having the above moisture content includes a method of storing a laminate in which a protective film is laminated on at least one surface of a polarizing element, or a polarizing plate constructed using a polarizing element, in an environment adjusted to the above temperature and relative humidity ranges for 10 minutes to 120 hours, or a method of heat treating the same at 30° C. to 90° C. When producing an image display device employing an interlayer filling configuration, a polarizing plate may be incorporated into the image display device, and the image display device in which the polarizing plate is incorporated may be stored in an environment adjusted to the above temperature and relative humidity ranges for 10 minutes to 3 hours or heated at 30° C. to 90° C., and then a front panel may be attached.
[0040] The moisture content of the polarizing element is preferably adjusted to be within the above numerical range at the stage of the material used to construct the polarizing plate, which is a polarizing element alone or a laminate of a polarizing element and a protective film. If the moisture content is adjusted after the polarizing plate is constructed, curling may become too large, and problems may easily occur when the polarizing plate is attached to an image display cell. By constructing a polarizing plate using a polarizing element that has been adjusted to have the above moisture content at the stage of the material before the polarizing plate is constructed, a polarizing plate having a polarizing element whose moisture content satisfies the above numerical range can be easily constructed. The moisture content of the polarizing element in the polarizing plate may be adjusted to be within the above numerical range while the polarizing plate is attached to the image display cell. In this case, the polarizing plate is less likely to curl because it is attached to the image display cell.
[0041] (Feature (b)) In the case of having the characteristic (b), the moisture content of the polarizing plate is equal to or higher than the equilibrium moisture content at a temperature of 20° C. and a relative humidity of 30%, and equal to or lower than the equilibrium moisture content at a temperature of 20° C. and a relative humidity of 50%. The moisture content of the polarizing plate is preferably equal to or lower than the equilibrium moisture content at a temperature of 20° C. and a relative humidity of 45%, more preferably equal to or lower than the equilibrium moisture content at a temperature of 20° C. and a relative humidity of 42%, and even more preferably equal to or lower than the equilibrium moisture content at a temperature of 20° C. and a relative humidity of 38%. If the moisture content of the polarizing plate is lower than the equilibrium moisture content at a temperature of 20° C. and a relative humidity of 30%, the handling property of the polarizing plate is deteriorated and the polarizing plate is easily cracked. If the moisture content of the polarizing plate is higher than the equilibrium moisture content at a temperature of 20° C. and a relative humidity of 50%, the transmittance of the polarizing element is easily decreased. It is presumed that the high moisture content of the polarizing plate makes it easier for the PVA-based resin to be polyenized.
[0042] As a method for checking whether the moisture content of a polarizing plate is within the range of equal to or greater than the equilibrium moisture content at a temperature of 20°C and a relative humidity of 30% and equal to or less than the equilibrium moisture content at a temperature of 20°C and a relative humidity of 50%, the polarizing plate can be stored in an environment adjusted to the above temperature and relative humidity ranges, and if there is no change in mass for a certain period of time, it can be considered that the polarizing plate has reached equilibrium with the environment. Alternatively, the equilibrium moisture content of the polarizing plate in an environment adjusted to the above temperature and relative humidity ranges can be calculated in advance, and the moisture content of the polarizing plate can be compared with the previously calculated equilibrium moisture content.
[0043] Methods for producing a polarizing plate having a moisture content equal to or greater than the equilibrium moisture content at a temperature of 20°C and a relative humidity of 30% and equal to or less than the equilibrium moisture content at a temperature of 20°C and a relative humidity of 50% include, but are not limited to, a method in which the polarizing plate is stored in an environment adjusted to the above-mentioned temperature and relative humidity range for 10 minutes to 3 hours, or a method in which the polarizing plate is heated at 30°C to 90°C.
[0044] When producing an image display device that employs an interlayer filling configuration, a polarizing plate may be incorporated into the image display device, and the image display device with the polarizing plate incorporated therein may be stored in an environment adjusted to the above-mentioned temperature and relative humidity ranges for 10 minutes to 3 hours or heated to 30°C to 90°C, and then a front panel may be attached to the image display device.
[0045] (Method of manufacturing polarizing element) The method for producing the polarizing element is not particularly limited, but typical methods include a method in which a PVA-based resin film that has already been wound into a roll is sent out and stretched, dyed, crosslinked, and the like to produce the polarizing element (hereinafter referred to as "production method 1"), and a method including a step of applying a coating liquid containing a PVA-based resin onto a substrate film to form a PVA-based resin layer as a coating layer, and stretching the resulting laminate (hereinafter referred to as "production method 2").
[0046] Production method 1 can include a step of uniaxially stretching a PVA-based resin film, a step of dyeing the PVA-based resin film with a dichroic dye such as iodine to adsorb the dichroic dye, a step of treating the PVA-based resin film with the adsorbed dichroic dye with an aqueous boric acid solution, and a step of washing with water after the treatment with the aqueous boric acid solution.
[0047] The swelling step is a treatment step in which the PVA-based resin film is immersed in a swelling bath. The swelling step can remove dirt and blocking agents on the surface of the PVA-based resin film, and can also suppress uneven dyeing by swelling the PVA-based resin film. A medium mainly composed of water, such as water, distilled water, or pure water, is usually used for the swelling bath. The swelling bath may contain surfactants, alcohol, or the like, as appropriate, according to a conventional method. In order to control the potassium content of the polarizing element, potassium iodide may be used in the swelling bath. In this case, the concentration of potassium iodide in the swelling bath is preferably 1.5% by mass or less, more preferably 1.0% by mass or less, and even more preferably 0.5% by mass or less.
[0048] The temperature of the swelling bath is preferably about 10° C. to about 60° C., more preferably about 15° C. to about 45° C., and even more preferably about 18° C. to about 30° C. The immersion time in the swelling bath cannot be determined in general because the degree of swelling of the PVA-based resin film is affected by the temperature of the swelling bath, but is preferably about 5 seconds to about 300 seconds, more preferably about 10 seconds to about 200 seconds, and even more preferably about 20 seconds to about 100 seconds. The swelling step may be carried out only once, or may be carried out multiple times as necessary.
[0049] The dyeing process is a treatment process in which the PVA-based resin film is immersed in a dye bath (iodine solution), and a dichroic dye such as iodine can be adsorbed and oriented on the PVA-based resin film. The iodine solution is usually preferably an aqueous iodine solution, and contains iodine and an iodide as a dissolving agent. Examples of iodides include potassium iodide, lithium iodide, sodium iodide, zinc iodide, aluminum iodide, lead iodide, copper iodide, barium iodide, calcium iodide, tin iodide, and titanium iodide. Among these, potassium iodide is preferred from the viewpoint of controlling the potassium content in the polarizing element.
[0050] The concentration of iodine in the dye bath is preferably about 0.01% by mass to about 1% by mass, more preferably about 0.02% by mass to about 0.5% by mass, and the concentration of iodide in the dye bath is preferably about 0.01% by mass to about 10% by mass, more preferably about 0.05% by mass to about 5% by mass, and even more preferably about 0.1% by mass to about 3% by mass.
[0051] The temperature of the dye bath is preferably about 10° C. to 50° C., more preferably about 15° C. to 45° C., and even more preferably about 18° C. to 30° C. The immersion time in the dye bath cannot be determined in general because the degree of dyeing of the PVA-based resin film is affected by the temperature of the dye bath, but is preferably about 10 seconds to 300 seconds, and more preferably about 20 seconds to 240 seconds. The dyeing process may be carried out only once, or may be carried out multiple times as necessary.
[0052] The crosslinking step is a treatment step in which the PVA-based resin film dyed in the dyeing step is immersed in a treatment bath (crosslinking bath) containing a boron compound, and the boron compound crosslinks the polyvinyl alcohol-based resin film, allowing iodine molecules or dye molecules to be adsorbed to the crosslinked structure. Examples of the boron compound include boric acid, borate salts, and borax. The crosslinking bath is generally an aqueous solution, but may also be a mixed solution of water and an organic solvent miscible with water. The crosslinking bath preferably contains potassium iodide from the viewpoint of controlling the potassium content in the polarizing element.
[0053] In the crosslinking bath, the concentration of the boron compound is preferably about 1% by mass to about 15% by mass, more preferably about 1.5% by mass to about 10% by mass, and more preferably about 2% by mass to about 5% by mass. When potassium iodide is used in the crosslinking bath, the concentration of potassium iodide in the crosslinking bath is preferably about 1% by mass to about 15% by mass, more preferably about 1.5% by mass to about 10% by mass, and more preferably about 2% by mass to about 5% by mass.
[0054] The temperature of the crosslinking bath is preferably about 20° C. to about 70° C., more preferably about 30° C. to about 60° C. The immersion time in the crosslinking bath cannot be determined in general because the degree of crosslinking of the PVA resin film is affected by the temperature of the crosslinking bath, but is preferably about 5 seconds to about 300 seconds, more preferably about 10 seconds to about 200 seconds. The crosslinking step may be carried out only once, or may be carried out multiple times as necessary.
[0055] The stretching process is a process for stretching the PVA-based resin film at least in one direction to a predetermined magnification. In general, the PVA-based resin film is uniaxially stretched in the conveying direction (longitudinal direction). There are no particular limitations on the stretching method, and either a wet stretching method or a dry stretching method can be used. The stretching process may be carried out only once, or may be carried out multiple times as necessary. The stretching process may be carried out at any stage in the production of a polarizing element.
[0056] The treatment bath (stretching bath) in the wet stretching method can usually use a solvent such as water or a mixed solution of water and an organic solvent miscible with water. The stretching bath preferably contains potassium iodide from the viewpoint of controlling the content of potassium in the polarizing element. When potassium iodide is used in the stretching bath, the concentration of potassium iodide in the stretching bath is preferably about 1% by mass to 15% by mass, more preferably about 2% by mass to 10% by mass, and more preferably about 3% by mass to 6% by mass. The treatment bath (stretching bath) can contain a boron compound from the viewpoint of suppressing film breakage during stretching. When a boron compound is contained, the concentration of the boron compound in the stretching bath is preferably about 1% by mass to 15% by mass, more preferably about 1.5% by mass to 10% by mass, and more preferably about 2% by mass to 5% by mass.
[0057] The temperature of the stretching bath is preferably about 25° C. to about 80° C., more preferably about 40° C. to about 75° C., and even more preferably about 50° C. to about 70° C. The immersion time in the stretching bath cannot be determined in general because the degree of stretching of the PVA-based resin film is affected by the temperature of the stretching bath, but is preferably about 10 seconds to about 800 seconds, and more preferably about 30 seconds to about 500 seconds. The stretching treatment in the wet stretching method may be performed together with one or more treatment steps of a swelling step, a dyeing step, a crosslinking step, and a washing step.
[0058] Examples of the dry stretching method include a roll-to-roll stretching method, a heated roll stretching method, a compression stretching method, etc. The dry stretching method may be carried out together with a drying step.
[0059] The total stretching ratio (cumulative stretching ratio) applied to the polyvinyl alcohol-based resin film can be appropriately set depending on the purpose, but is preferably about 2 to 7 times, more preferably about 3 to 6.8 times, and even more preferably about 3.5 to 6.5 times.
[0060] The cleaning step is a treatment step in which the polyvinyl alcohol-based resin film is immersed in a cleaning bath, and foreign matter remaining on the surface of the polyvinyl alcohol-based resin film can be removed. The cleaning bath is usually made of a medium mainly composed of water, such as water, distilled water, or pure water. In addition, from the viewpoint of controlling the potassium content in the polarizing element, it is preferable to use potassium iodide in the cleaning bath. In this case, the concentration of potassium iodide in the cleaning bath is preferably about 1% by mass or more and 10% by mass or less, more preferably about 1.5% by mass or more and 4% by mass or less, and even more preferably about 1.8% by mass or more and 3.8% by mass or less.
[0061] The temperature of the cleaning bath is preferably about 5° C. to about 50° C., more preferably about 10° C. to about 40° C., and even more preferably about 15° C. to about 30° C. The immersion time in the cleaning bath cannot be determined in general because the degree of cleaning of the PVA-based resin film is affected by the temperature of the cleaning bath, but is preferably about 1 second to about 100 seconds, more preferably about 2 seconds to about 50 seconds, and even more preferably about 3 seconds to about 20 seconds. The cleaning step may be carried out only once, or may be carried out multiple times as necessary.
[0062] The drying step is a step of drying the PVA-based resin film washed in the washing step to obtain a polarizing element. The drying can be performed by any appropriate method, for example, natural drying, air drying, or heat drying.
[0063] The manufacturing method 2 can be produced through the steps of applying a coating solution containing a PVA resin onto a substrate film, uniaxially stretching the resulting laminated film, dyeing the PVA resin layer of the uniaxially stretched laminated film with a dichroic dye to adsorb it to form a polarizing element, treating the film with the adsorbed dichroic dye with an aqueous boric acid solution, and washing with water after the treatment with the aqueous boric acid solution. The substrate film used to form the polarizing element may be used as a protective layer for the polarizing element. If necessary, the substrate film may be peeled off and removed from the polarizing element.
[0064] <Transparent protective film> The transparent protective film (hereinafter, simply referred to as "protective film") used in this embodiment is attached to at least one surface of the polarizing element via an adhesive layer. This transparent protective film is attached to one or both surfaces of the polarizing element, but is preferably attached to both surfaces.
[0065] The protective film may have other optical functions at the same time, and may be formed into a laminated structure in which multiple layers are laminated. The thickness of the protective film is preferably thin from the viewpoint of optical properties, but if it is too thin, the strength decreases and the processability is poor. The appropriate thickness is 5 μm or more and 100 μm or less, preferably 10 μm or more and 80 μm or less, and more preferably 15 μm or more and 70 μm or less.
[0066] The protective film may be a cellulose acylate film, a film made of a polycarbonate resin, a film made of a cycloolefin resin such as norbornene, a (meth)acrylic polymer film, a polyester resin film such as polyethylene terephthalate, etc. When a protective film is attached to both sides of a polarizing element using a water-based adhesive such as a PVA adhesive, it is preferable that the protective film on at least one side is either a cellulose acylate film or a (meth)acrylic polymer film in terms of moisture permeability, and among these, a cellulose acylate film is preferable.
[0067] At least one of the protective films may have a retardation function for the purpose of compensating for a viewing angle. In that case, the protective film itself may have a retardation function, may have a separate retardation layer, or may be a combination of both. The film having a retardation function may be directly attached to the polarizing element via an adhesive, or may be attached via a pressure-sensitive adhesive or adhesive via another protective film attached to the polarizing element.
[0068] <Adhesive layer> The adhesive that constitutes the adhesive layer for bonding the protective film to the polarizing element is an adhesive that contains a urea-based compound and cyclodextrins. The adhesive can be a water-based adhesive, a solvent-based adhesive, an active energy ray curing adhesive, or the like, but is preferably a water-based adhesive and preferably contains a PVA-based resin. By using an adhesive that contains a urea-based compound and cyclodextrins, the decrease in transmittance of the polarizing plate in a high-temperature environment can be suppressed.
[0069] The thickness of the adhesive when applied can be set to any value, for example, so that an adhesive layer having a desired thickness is obtained after curing or heating (drying). The thickness of the adhesive layer made of the adhesive is preferably 0.01 μm or more and 7 μm or less, more preferably 0.01 μm or more and 5 μm or less, even more preferably 0.01 μm or more and 2 μm or less, and most preferably 0.01 μm or more and 1 μm or less.
[0070] The following description of the adhesive is a description of the preferred range in the case where the polarizing element does not contain a urea-based compound and a cyclodextrin when the polarizing element is manufactured. When the polarizing element contains a urea-based compound or a cyclodextrin, the following values may be adjusted appropriately. As specific examples of the urea-based compound and the cyclodextrin, the examples of the urea-based compound and the cyclodextrin contained in the polarizing element described above can be applied as they are. In the process of forming an adhesive layer through a drying process when adhering the polarizing element and the protective film, a part of the urea-based compound and a part of the cyclodextrin may migrate from the adhesive layer to the polarizing element, etc.
[0071] In the case where the adhesive is a water-based adhesive containing a PVA-based resin, the content of the urea-based compound is preferably 0.1 parts by mass or more and 400 parts by mass or less, more preferably 1 part by mass or more and 200 parts by mass or less, and even more preferably 3 parts by mass or more and 100 parts by mass or less, relative to 100 parts by mass of the PVA-based resin. If it is less than 0.1 parts by mass, the effect of suppressing the polyenization of the polarizing element in a high-temperature environment may not be sufficient. On the other hand, if it exceeds 400 parts by mass, urea may precipitate after the polarizing plate is produced, and the haze may increase.
[0072] In the case where the adhesive is a water-based adhesive containing a PVA-based resin, the content of cyclodextrins is preferably 1 part by mass or more and 50 parts by mass or less, more preferably 1.5 parts by mass or more and 40 parts by mass or less, and even more preferably 2 parts by mass or more and 35 parts by mass or less, relative to 100 parts by mass of the PVA-based resin. If the content is less than 1 part by mass, the effect of suppressing the polyenization of the polarizing element in a high-temperature environment may not be sufficient. On the other hand, if the content exceeds 50 parts by mass, the cyclodextrins may precipitate after the polarizing plate is produced.
[0073] In a configuration in which transparent protective films are bonded to both sides of a polarizing element via adhesive layers, if the polarizing element has not been treated to contain a urea-based compound and cyclodextrins, only one of the adhesive layers on both sides of the polarizing element may be a layer containing a urea-based compound and cyclodextrins, but it is preferable that both adhesive layers on both sides are layers containing a urea-based compound and cyclodextrins.
[0074] In order to meet the demand for thinner polarizing plates, polarizing plates having a transparent protective film only on one side of a polarizing element have been developed. In this configuration, the transparent protective film is also laminated via an adhesive layer containing a urea-based compound and cyclodextrins. As a method for producing a polarizing plate having a transparent protective film only on one side of such a polarizing element, a method is considered in which a polarizing plate having a transparent protective film attached to both sides via an adhesive layer is first produced, and then one of the transparent protective films is peeled off. When such a production method is used, only one of the adhesive layers may contain a urea-based compound and cyclodextrins, but it is preferable that both adhesive layers on both sides are layers containing a urea-based compound and cyclodextrins. When only one adhesive layer contains a urea-based compound and cyclodextrins, it is preferable that the adhesive layer on the film side that is not peeled off contains a urea-based compound and cyclodextrins.
[0075] (Water-based adhesive) As the aqueous adhesive, any suitable aqueous adhesive may be used, but preferably, an aqueous adhesive containing a PVA resin (PVA adhesive) is used. From the viewpoint of adhesiveness, the average polymerization degree of the PVA resin contained in the aqueous adhesive is preferably about 100 to 5500, more preferably 1000 to 4500. From the viewpoint of adhesiveness, the average saponification degree is preferably about 85 mol% to 100 mol%, more preferably 90 mol% to 100 mol%.
[0076] The PVA resin contained in the aqueous adhesive is preferably one containing an acetoacetyl group, because it has excellent adhesion between the PVA resin layer and the protective film and excellent durability. The acetoacetyl group-containing PVA resin can be obtained, for example, by reacting a PVA resin with diketene by any method. The acetoacetyl group modification degree of the acetoacetyl group-containing PVA resin is typically 0.1 mol% or more, preferably about 0.1 mol% or more and 20 mol% or less. The resin concentration of the aqueous adhesive is preferably 0.1 mass% or more and 15 mass% or less, more preferably 0.5 mass% or more and 10 mass% or less.
[0077] The water-based adhesive may contain a crosslinking agent. Known crosslinking agents may be used as the crosslinking agent. Examples of the crosslinking agent include water-soluble epoxy compounds, dialdehydes, and isocyanates.
[0078] When the PVA-based resin is an acetoacetyl group-containing PVA-based resin, the crosslinking agent is preferably any one of glyoxal, glyoxylate, and methylolmelamine, more preferably any one of glyoxal and glyoxylate, and particularly preferably glyoxal.
[0079] The aqueous adhesive may also contain an organic solvent. The organic solvent is preferably an alcohol in terms of its miscibility with water, and among the alcohols, methanol or ethanol is more preferable. The concentration of methanol in the aqueous adhesive is preferably 10% by mass or more and 70% by mass or less, more preferably 15% by mass or more and 60% by mass or less, and even more preferably 20% by mass or more and 60% by mass or less. By having a methanol concentration of 10% by mass or more, it is easier to suppress polyenation of the PVA resin in a high-temperature environment. In addition, by having a methanol content of 70% by mass or less, it is possible to suppress deterioration of the hue. Some urea derivatives have low solubility in water, but have sufficient solubility in alcohol. In that case, one of the preferred embodiments is to dissolve a urea compound in alcohol to prepare an alcohol solution of the urea compound, and then add the alcohol solution of the urea compound to the PVA aqueous solution to prepare the adhesive.
[0080] (Active energy ray curing adhesive) The active energy ray curable adhesive is an adhesive that is cured by irradiation with active energy rays such as ultraviolet rays, and examples thereof include an adhesive containing a polymerizable compound and a photopolymerization initiator, an adhesive containing a photoreactive resin, and an adhesive containing a binder resin and a photoreactive crosslinking agent. Examples of the polymerizable compound include photopolymerizable monomers such as photocurable epoxy monomers, photocurable acrylic monomers, and photocurable urethane monomers, and oligomers derived from these monomers. Examples of the photopolymerization initiator include compounds containing a substance that generates active species such as neutral radicals, anion radicals, and cation radicals when irradiated with active energy rays such as ultraviolet rays.
[0081] <Urea-based compound-containing layer> The urea compound and the cyclodextrins are not limited to those contained in the adhesive layer as described above, and may be contained in a layer other than the adhesive layer from the viewpoint of improving the high-temperature durability of the polarizing plate. In a polarizing plate having a transparent protective film only on one side, a cured layer may be laminated on the side of the polarizing element opposite the transparent protective film from the viewpoint of improving physical strength.
[0082] In this embodiment, such a cured layer may contain a urea-based compound and cyclodextrins to form a urea-based compound-containing layer. Usually, such a cured layer is formed from a curable composition containing an organic solvent, but paragraphs
[0020] to
[0042] of JP2017-075986A disclose a method for forming such a cured layer from an aqueous solution of an active energy ray-curable polymer composition. Water-soluble urea-based compounds and cyclodextrins may be contained in such a composition.
[0083] The urea compound-containing layer preferably contains at least one urea compound, at least one cyclodextrin, and a binder, such as a polymer binder, a thermosetting resin binder, or an active energy ray-curable resin binder, and any of these binders can be preferably used.
[0084] The thickness of the urea compound-containing layer is preferably 0.1 μm or more and 20 μm or less, more preferably 0.5 μm or more and 15 μm or less, and further preferably 1 μm or more and 10 μm or less.
[0085] [Method of manufacturing polarizing plate] The manufacturing method of the polarizing plate of this embodiment may include a moisture content adjusting step and a lamination step. In the moisture content adjusting step, when a polarizing plate having the characteristic (a) is manufactured, the moisture content of the polarizing element is adjusted so that the moisture content of the polarizing element is equal to or higher than the equilibrium moisture content at a temperature of 20° C. and a relative humidity of 30% and equal to or lower than the equilibrium moisture content at a temperature of 20° C. and a relative humidity of 50%. The moisture content of the polarizing element can be adjusted according to the description of the moisture content of the polarizing element described above. In the moisture content adjusting step, when a polarizing plate having the characteristic (b) is manufactured, the moisture content of the polarizing plate is adjusted so that the moisture content of the polarizing plate is equal to or higher than the equilibrium moisture content at a temperature of 20° C. and a relative humidity of 30% and equal to or lower than the equilibrium moisture content at a temperature of 20° C. and a relative humidity of 50%. The moisture content of the polarizing plate can be adjusted according to the description of the moisture content of the polarizing plate described above. In the lamination step, the polarizing element and the transparent protective film are laminated via the adhesive layer. In the lamination step, for example, a polarizing element that has not been treated to contain a urea compound and a cyclodextrin is bonded to a transparent protective film using an adhesive containing a urea compound and a cyclodextrin. The order of the moisture content adjustment step and the lamination step is not limited, and the moisture content adjustment step and the lamination step may be performed in parallel.
[0086] [Image display device configuration] The polarizing plate of the present embodiment is used in various image display devices such as liquid crystal display devices and organic EL display devices. In the case of an image display device having an interlayer filling configuration in which both sides of the polarizing plate are in contact with a layer other than an air layer, specifically a solid layer such as an adhesive layer, the transmittance is likely to decrease in a high-temperature environment. In the image display device using the polarizing plate of the present embodiment, even if the interlayer filling configuration is used, the decrease in the transmittance of the polarizing plate in a high-temperature environment can be suppressed. An example of the image display device is a configuration having an image display cell, a first adhesive layer laminated on the viewing side surface of the image display cell, and a polarizing plate laminated on the viewing side surface of the first adhesive layer. Such an image display device may further have a second adhesive layer laminated on the viewing side surface of the polarizing plate and a transparent member laminated on the viewing side surface of the second adhesive layer. In particular, the polarizing plate of the present embodiment is suitably used in an image display device having an interlayer filling configuration in which a transparent member is arranged on the viewing side of the image display device, the polarizing plate and the image display cell are bonded together by the first adhesive layer, and the polarizing plate and the transparent member are bonded together by the second adhesive layer. In this specification, either or both of the first pressure-sensitive adhesive layer and the second pressure-sensitive adhesive layer may be simply referred to as an “adhesive layer.” Note that the member used for bonding the polarizing plate and the image display cell, and the member used for bonding the polarizing plate and the transparent member are not limited to a pressure-sensitive adhesive layer, and may be an adhesive layer.
[0087] <Image display cell> Examples of the image display cell include a liquid crystal cell and an organic EL cell. The liquid crystal cell may be a reflective liquid crystal cell that uses external light, a transmissive liquid crystal cell that uses light from a light source such as a backlight, or a semi-transmissive semi-reflective liquid crystal cell that uses both external light and light from a light source. When the liquid crystal cell uses light from a light source, the image display device (liquid crystal display device) has a polarizing plate disposed on the opposite side to the viewing side of the image display cell (liquid crystal cell), and further has a light source disposed thereon. The polarizing plate on the light source side and the liquid crystal cell are preferably bonded together via an appropriate adhesive layer. The driving method of the liquid crystal cell may be any type, such as VA mode, IPS mode, TN mode, STN mode, or bend orientation (π type).
[0088] As the organic EL cell, a light-emitting body (organic electroluminescence light-emitting body) is preferably formed by sequentially laminating a transparent electrode, an organic light-emitting layer, and a metal electrode on a transparent substrate. The organic light-emitting layer is a laminate of various organic thin films, and various layer configurations can be adopted, such as a laminate of a hole injection layer made of a triphenylamine derivative or the like and a light-emitting layer made of a fluorescent organic solid such as anthracene, a laminate of such a light-emitting layer and an electron injection layer made of a perylene derivative or the like, or a laminate of a hole injection layer, a light-emitting layer, and an electron injection layer.
[0089] <Laminating the image display cell and the polarizing plate> A pressure-sensitive adhesive layer (pressure-sensitive adhesive sheet) is preferably used for bonding the image display cell and the polarizing plate. Among them, a method of bonding a polarizing plate with a pressure-sensitive adhesive layer, in which a pressure-sensitive adhesive layer is attached to one side of the polarizing plate, to the image display cell is preferred from the viewpoint of workability and the like. The pressure-sensitive adhesive layer can be attached to the polarizing plate by a suitable method. Examples of such a method include a method of preparing a pressure-sensitive adhesive solution of about 10% by mass to 40% by mass by dissolving or dispersing a base polymer or a composition thereof in a solvent consisting of a single or mixture of suitable solvents such as toluene and ethyl acetate, and directly attaching the solution to the polarizing plate by a suitable spreading method such as a casting method or a coating method, and a method of forming a pressure-sensitive adhesive layer on a separator and transferring the solution to the polarizing plate.
[0090] <Adhesive layer> The adhesive layer may be composed of one layer or two or more layers, but is preferably composed of one layer. The adhesive layer may be composed of an adhesive composition mainly composed of (meth)acrylic resin, rubber resin, urethane resin, ester resin, silicone resin, or polyvinyl ether resin. Among them, an adhesive composition having a (meth)acrylic resin as a base polymer, which is excellent in transparency, weather resistance, heat resistance, etc., is preferable. The adhesive composition may be of an active energy ray curing type or a heat curing type.
[0091] As the (meth)acrylic resin (base polymer) used in the pressure-sensitive adhesive composition, a polymer or copolymer containing one or more monomers of (meth)acrylic acid esters such as butyl (meth)acrylate, ethyl (meth)acrylate, isooctyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, etc. is preferably used. A polar monomer is preferably copolymerized in the base polymer. Examples of the polar monomer include monomers having a carboxyl group, a hydroxyl group, an amide group, an amino group, an epoxy group, etc., such as a (meth)acrylic acid compound, a 2-hydroxypropyl (meth)acrylate compound, a hydroxyethyl (meth)acrylate compound, a (meth)acrylamide compound, an N,N-dimethylaminoethyl (meth)acrylate compound, and a glycidyl (meth)acrylate compound.
[0092] The adhesive composition may contain only the base polymer, but usually further contains a crosslinking agent. Examples of the crosslinking agent include a divalent or higher metal ion that forms a carboxylate metal salt with a carboxyl group, a polyamine compound that forms an amide bond with a carboxyl group, a polyepoxy compound or polyol that forms an ester bond with a carboxyl group, and a polyisocyanate compound that forms an amide bond with a carboxyl group. Among them, a polyisocyanate compound is preferred.
[0093] The active energy ray curable adhesive composition has a property of being cured by irradiation with active energy rays such as ultraviolet rays and electron beams, and has a property of being able to adhere to an adherend such as a film even before irradiation with active energy rays, and is able to adjust the adhesive strength by being cured by irradiation with active energy rays. The active energy ray curable adhesive composition is preferably an ultraviolet ray curable type. The active energy ray curable adhesive composition further contains an active energy ray polymerizable compound in addition to a base polymer and a crosslinking agent. If necessary, a photopolymerization initiator, a photosensitizer, etc. may be contained.
[0094] The pressure-sensitive adhesive composition can contain additives such as microparticles for imparting light scattering properties, beads (resin beads, glass beads, etc.), glass fibers, resins other than the base polymer, tackifiers, fillers (metal powders and other inorganic powders, etc.), antioxidants, UV absorbers, dyes, pigments, colorants, defoamers, corrosion inhibitors, and photopolymerization initiators.
[0095] The adhesive layer can be formed by applying an organic solvent dilution of the adhesive composition onto the surface of a substrate film, an image display cell or a polarizing plate, and drying it.The substrate film is generally a thermoplastic resin film, and a typical example thereof is a release-treated separate film.The separate film can be, for example, a film made of a resin such as polyethylene terephthalate, polybutylene terephthalate, polycarbonate, polyarene, etc., and the surface on which the adhesive layer is formed is subjected to a release treatment such as silicone treatment.
[0096] The pressure-sensitive adhesive composition may be directly applied to the release-treated surface of the separate film to form a pressure-sensitive adhesive layer, and the pressure-sensitive adhesive layer with the separate film may be laminated on the surface of the polarizer.The pressure-sensitive adhesive composition may be directly applied to the surface of the polarizing plate to form a pressure-sensitive adhesive layer, and the separate film may be laminated on the outer surface of the pressure-sensitive adhesive layer.
[0097] When providing the pressure-sensitive adhesive layer on the surface of the polarizing plate, it is preferable to subject the bonding surface of the polarizing plate and / or the bonding surface of the pressure-sensitive adhesive layer to a surface activation treatment such as plasma treatment or corona treatment, and it is more preferable to subject the layer to corona treatment.
[0098] Alternatively, a pressure-sensitive adhesive composition may be applied onto a second separate film to form a pressure-sensitive adhesive layer, a separate film may be laminated onto the formed pressure-sensitive adhesive layer to prepare a pressure-sensitive adhesive sheet, and the pressure-sensitive adhesive layer with the separate film after peeling the second separate film from the pressure-sensitive adhesive sheet may be laminated onto a polarizing plate. The second separate film used has a weaker adhesion to the pressure-sensitive adhesive layer than the separate film and is therefore easier to peel off.
[0099] The thickness of the pressure-sensitive adhesive layer is not particularly limited, but is, for example, preferably from 1 μm to 100 μm, more preferably from 3 μm to 50 μm, and may be 20 μm or more.
[0100] <Transparent material> Examples of the transparent member arranged on the viewing side of the image display device include a transparent plate (window layer) and a touch panel. As the transparent plate, a transparent plate having appropriate mechanical strength and thickness is used. Examples of such transparent plates include transparent resin plates such as polyimide resin, acrylic resin, and polycarbonate resin, and glass plates. A functional layer such as an anti-reflection layer may be laminated on the viewing side of the transparent plate. In addition, when the transparent plate is a transparent resin plate, a hard coat layer may be laminated to increase physical strength, or a low moisture permeable layer may be laminated to reduce moisture permeability. As the touch panel, various touch panels such as resistive film type, capacitive type, optical type, and ultrasonic type, and glass plate or transparent resin plate having a touch sensor function are used. When a capacitive type touch panel is used as the transparent member, it is preferable that a transparent plate made of glass or transparent resin plate is provided on the viewing side further than the touch panel.
[0101] <Laminating a polarizing plate to a transparent material> A pressure sensitive adhesive or an active energy ray curable adhesive is preferably used for bonding the polarizing plate and the transparent member. When a pressure sensitive adhesive is used, the pressure sensitive adhesive can be applied by an appropriate method. As a specific application method, for example, the application method of the pressure sensitive adhesive layer used for bonding the image display cell and the polarizing plate described above can be mentioned.
[0102] When an active energy ray curable adhesive is used, a method is preferably used in which a dam material is provided so as to surround the periphery of the image display panel in order to prevent the adhesive solution from spreading before curing, a transparent member is placed on the dam material, and the adhesive solution is then poured in. After the adhesive solution is poured, alignment and degassing are performed as necessary, and then the adhesive solution is irradiated with active energy rays to cause curing. EXAMPLES
[0103] The present invention will be specifically described below based on examples. The materials, reagents, amounts of substances and their ratios, operations, etc. shown in the following examples can be appropriately changed without departing from the spirit of the present invention. Therefore, the present invention is not limited to the following examples.
[0104] <Preparation of Polarizing Element A> A 40 μm thick PVA film was prepared, which was made of PVA with an average degree of polymerization of about 2400 and a degree of saponification of 99.9 mol% or more. This PVA film was uniaxially stretched by about 5 times in a dry manner, and was then immersed in pure water at 60° C. for 1 minute while maintaining tension. The PVA film was then immersed in an aqueous solution with a weight ratio of iodine / potassium iodide / water of 0.05 / 5 / 100 at 28° C. for 60 seconds. The PVA film was then immersed in an aqueous solution with a weight ratio of potassium iodide / boric acid / water of 8.5 / 8.5 / 100 at 72° C. for 300 seconds. The PVA film was then washed with pure water at 26° C. for 20 seconds, and then dried at 65° C. to obtain a polarizing element A with a thickness of 15 μm, in which iodine was adsorbed and aligned in the PVA. A digital micrometer "MH-15M" manufactured by Nikon Corporation was used to measure the thickness of the polarizing element.
[0105] <Preparation of Adhesives 1 to 7> (Preparation of PVA solution A for adhesive) 50 g of modified PVA resin containing acetoacetyl groups ("Gosenex Z-410" manufactured by Mitsubishi Chemical Corporation) was dissolved in 950 g of pure water. This solution was heated at 90°C for 2 hours and then cooled to room temperature to obtain PVA solution A for adhesive.
[0106] (Preparation of Adhesives 1 to 7) PVA solution A, a urea compound, cyclodextrins, and pure water were mixed so as to contain 3.0 mass % of PVA solution A and the amounts of the urea compound and cyclodextrins shown in Table 1, to prepare adhesives 1 to 7.
[0107] [Table 1]
[0108] <Preparing transparent protective film A> A commercially available cellulose acylate film TD40 (manufactured by Fujifilm Corporation, film thickness 40 μm) was immersed in a 1.5 mol / L NaOH aqueous solution (saponification solution) maintained at 55° C. for 2 minutes, and then washed with water. Thereafter, the film was immersed in a 0.05 mol / L sulfuric acid aqueous solution at 25° C. for 30 seconds, and then washed under running water for 30 seconds to neutralize the film. After removing the water by draining it three times with an air knife, the film was allowed to stay in a drying zone at 70° C. for 15 seconds and dried to obtain a saponified transparent protective film A.
[0109] <Preparation of Polarizing Plates 1 to 7> Transparent protective film A was attached to both sides of polarizing element A via adhesive 1. A roll laminator was used for the lamination. This laminate was dried at 80°C for 5 minutes to obtain polarizing plate 1. The coating thickness of the adhesive layer was adjusted so that the thickness after drying was 50 nm on both sides.
[0110] Polarizing plates 2 to 7 were obtained by changing adhesive 1 in the production of polarizing plate 1 to adhesives 2 to 7.
[0111] <Preparation of Optical Laminates 1 to 7> An acrylic adhesive (Lintec Corporation, product number: #7) was applied to both sides of the polarizing plate 1 prepared above, thereby preparing an optical laminate 1 having an adhesive layer with a thickness of 25 μm on both sides.
[0112] In the production of the optical laminate 1, the polarizing plate 1 was changed to polarizing plates 2 to 7, and optical laminates 2 to 7 were obtained.
[0113] <High temperature durability evaluation> (Preparation of evaluation samples) The optical laminates 1 to 7 were cut to a size of 50 mm x 100 mm so that the absorption axis was parallel to the long side. An alkali-free glass ("EAGLE XG" manufactured by Corning) was attached to the surface of each adhesive to prepare an evaluation sample. In order to adjust the moisture content of the optical laminate, the optical laminate was stored for 72 hours under conditions of a temperature of 20°C and a relative humidity of 35% before lamination with the glass plate. The weights of all samples were measured after 66 hours, 69 hours, and 72 hours of storage, and since there was no change, the moisture contents of the polarizing element, polarizing plate, and optical laminate were deemed to have reached the equilibrium moisture content at a temperature of 20°C and a relative humidity of 35%.
[0114] (Evaluation of unit transmittance after high temperature durability test (105℃)) The evaluation samples of the optical laminates 1 to 7 were subjected to a temperature of 50°C and a pressure of 5 kgf / cm 2 (490.3 kPa) for 1 hour, and then left for 24 hours in an environment with a temperature of 23°C and a relative humidity of 55%. The transmittance of the optical laminate at this time was measured and used as the initial value. It was then stored in a heated environment at a temperature of 105°C, and the transmittance was measured every 24 hours for 72 to 240 hours. The single transmittance was evaluated according to the following criteria, based on the time at which the transmittance had decreased by 5% or more from the initial value. The results are shown in Table 2. The decrease in transmittance after 240 hours is 5% or less: A The transmittance decreased by 5% or more after 120 to 240 hours: B The transmittance drops by 5% or more after 72 to 120 hours: C The transmittance decreases by 5% or more after 72 hours: D
[0115] [Table 2]
[0116] It was found that polarizing plates (optical laminates 1 to 4) in which a polarizing element and a transparent protective film are bonded together with an adhesive containing a urea-based compound and cyclodextrins are less likely to decrease in transmittance even when exposed to a high-temperature environment of 105°C, and have excellent high-temperature durability, compared to polarizing plates (optical laminates 5 to 7) in which the polarizing element and the transparent protective film are bonded together with an adhesive containing only a urea-based compound or cyclodextrins.
Claims
1. A polarizing plate comprising a polarizing element having a polyvinyl alcohol-based resin layer on which a dichroic dye is adsorbed and oriented, and a transparent protective film laminated on at least one surface of the polarizing element, the polarizing element and the transparent protective film are attached to each other by an adhesive layer formed from an adhesive containing a urea compound and a cyclodextrin; the urea-based compound is at least one selected from the group consisting of urea, urea derivatives, thiourea, and thiourea derivatives, The cyclodextrin is at least one selected from the group consisting of α-cyclodextrin and β-cyclodextrin.
2. The polarizing plate according to claim 1 , wherein the adhesive contains at least one urea-based compound selected from the group consisting of urea derivatives and thiourea derivatives.
3. The polarizing plate according to claim 1 , wherein the adhesive comprises a polyvinyl alcohol-based resin.
4. The polarizing plate according to claim 3 , wherein the adhesive contains the urea compound in an amount of 0.1 parts by mass to 400 parts by mass with respect to 100 parts by mass of the polyvinyl alcohol resin.
5. 5. The polarizing plate according to claim 3, wherein the adhesive contains the cyclodextrin in an amount of 1 part by mass to 50 parts by mass with respect to 100 parts by mass of the polyvinyl alcohol-based resin.
6. 6. The polarizing plate according to claim 1, wherein the adhesive layer has a thickness of 0.01 μm or more and 7 μm or less.
7. 7. The polarizing plate according to claim 1, wherein the moisture content of the polarizing element is equal to or higher than the equilibrium moisture content at a temperature of 20° C. and a relative humidity of 30% and equal to or lower than the equilibrium moisture content at a temperature of 20° C. and a relative humidity of 50%.
8. 7. The polarizing plate according to claim 1, wherein the moisture content of the polarizing plate is equal to or higher than the equilibrium moisture content at a temperature of 20° C. and a relative humidity of 30% and equal to or lower than the equilibrium moisture content at a temperature of 20° C. and a relative humidity of 50%.
9. The polarizing plate is used in an image display device, 9. The polarizing plate according to claim 1, wherein in the image display device, solid layers are provided on both sides of the polarizing plate in contact with each other.
10. An image display device comprising: an image display cell; a first pressure-sensitive adhesive layer laminated on a viewing side surface of the image display cell; and a polarizing plate according to any one of claims 1 to 9 laminated on the viewing side surface of the first pressure-sensitive adhesive layer.
11. The image display device according to claim 10 , further comprising: a second adhesive layer laminated on the viewer-side surface of the polarizing plate; and a transparent member laminated on the viewer-side surface of the second adhesive layer.
12. The image display device according to claim 11 , wherein the transparent member is a glass plate or a transparent resin plate.
13. The image display device according to claim 11 , wherein the transparent member is a touch panel.
Citation Information
Patent Citations
Liquid crystal panel support, electronic equipment having the same and manufacture of the same equipment
JP1999174417A
Polarizing plate equipped with protecting film, manufacturing method therefor, and image display device using polarizing plate
JP2005326531A
Liquid crystal display device and manufacturing method thereof
JP2012108452A
Polarizing plate, image display apparatus employing the same, and adhesive composition
JP2013050583A
Adhesive for polarizing plate
JP2014037477A
